Perturbation of ER-mitochondria crosstalk in bipolar disorder: effect of Sigma-1 receptor modulation - Cunha, Ana Rita Azevedo Henriques da (2021)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia